Challenges of antithrombotic therapy in the management of cardiovascular disease in patients with inherited bleeding disorders: A single‐centre experience. Issue 3 (22nd March 2021) - Cohen, Oliver C.; Bertelli, Michele; Manmathan, Gavin; Little, Callum; Riddell, Anne; Pollard, Debra; Aradom, Elsa; Mussara, Molly; Harrington, Chris; Kanagasabapathy, Pamela; De Silva, Ravi; Martin, Bruce; et al.
Abstract: Introduction: Cardiovascular events in patients with inherited bleeding disorders are challenging to manage. The risk of bleeding secondary to antithrombotic treatment must be balanced against the risk of thrombosis secondary to haemostatic therapy. Methods: Patients with inherited bleeding disorders with coronary artery bypass grafting (CABG), percutaneous coronary intervention (PCI) or atrial fibrillation (AF) from a single centre (2010–2018) are included. Results: A total of 11 patients undergoing CABG ( n = 3), PCI ( n = 5) or with AF ( n = 3) and a diagnosis of haemophilia A ( n = 8), haemophilia B ( n = 1), factor XI deficiency ( n = 1) and von Willebrand disease ( n = 1) managed by a multidisciplinary team are reported. In patients undergoing CABG, factor levels were normalized for 7–10 days with trough levels of 70–80% with severe patients continuing high‐dose factor prophylaxis (trough 20–30%) three weeks post‐operatively with daily aspirin. In a patient with mild haemophilia A and an inhibitor, recombinant factor VIIa dosing was monitored with thromboelastometry. For PCI, a 3rd‐generation drug‐eluting stent with one month of dual antiplatelet therapy in addition to high‐dose prophylaxis as needed was preferred. Patients with AF and severe haemophilia did not receive antithrombotic treatment, and a thrombin generation assay was used to guide heparin dosing in mild haemophilia. Conclusion: Our experience demonstrates the importance of interdisciplinary communication to identify strategies that decrease the risk of bleeding and thrombosis. The use of extended, increased intensity prophylaxis facilitated antiplatelet therapy. Global assays may help balance the intensity of haemostatic and antithrombotic treatment.